Calprotectin (S100A8/S100A9): a key protein between inflammation and cancer - Shabani, Fatemeh; Farasat, Alireza; Mahdavi, Majid; Gheibi, Nematollah (Inflammation research, 2018)
Background Calprotectin (S100A8/S100A9), a heterodimeric EF-hand Ca 2+ binding protein, are abundant in cytosol of neutrophils and are involved in inflammatory processes and several cancerous pathogens. Objective The purpose of the present systematic review is to evaluate the pro- and anti-tumorigenic functions of calprotectin and its relation to inflammation. Materials and methods We conducted a review of studies published in the Medline (1966–2018), Scopus (2004–2018), ClinicalTrials.gov (2008–2018) and Google Scholar (2004–2018) databases, combined with studies found in the reference lists of the included studies. Results Elevated levels of S100A8/S100A9 were detected in inflammation, neoplastic tumor cells and various human cancers. Recent data have explained that many cancers arise from sites of infection, chronic irritation, and inflammation. The inflammatory microenvironment which largely includes calprotectin, has an essential role on high producing of inflammatory factors and then on neoplastic process and metastasis. Conclusion Scientists have shown different outcomes in inflammation, malignancy and apoptosis whether the source of the aforementioned protein is extracellular or intracellular. These findings are offering new insights that anti-inflammatory therapeutic agents and anti-tumorigenic functions of calprotectin can lead to control cancer development.